ANTIMICROBIAL ACTIVITY OF HELIANTHUS ANNUS AGAINST SOME SELECTED HUMAN PATHOGENIC BACTERIA - Dr. Yugal Kishor Sarle (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Helianthus annus is a very useful medicine plant which found near rice field throughout in India. Whole plant Helianthus annus there are six crude extracts were prepared using different solvents by cold maceration method. Antimicrobial activity against Basillus subtilis, Klebsiella pneumonae and candida albicans were detected with extacts and Ciprofloxacine and fluconazole use as standard by cup plat agar diffusion method. The extracts were subjected to screening to detect potential antimicrobial activity against Basillus subtilis, Klebsiella pneumonae and candida albicans, Ciprofloxacin and Fluconazole as standard by cup plate agar diffusion method. In presence study, our aim was to find out the antimicrobial activity of different extracts of whole plant Helianthus annus. Some different extracts such as methanol, petroleum ether, chloroform and aqueous extract exhibits comparable antimicrobial activity with standard.